2009
DOI: 10.1007/s10661-009-1249-2
|View full text |Cite
|
Sign up to set email alerts
|

Indoor exposure to respirable particulate matter and particulate-phase PAHs in rural homes in North India

Abstract: In order to evaluate the exposure of the northern India rural population to polyaromatic hydrocarbon (PAH) inhalation, indoor pollution was assessed by collecting and analyzing the respirable particulate matter PM2.5 and PM10 in several homes of the village Bhithauli near Lucknow, UP. The home selection was determined by a survey. Given the nature of biomass used for cooking, homes were divided into two groups, one using all kinds of biomass and the second type using plant materials only. Indoor mean concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 19 publications
2
8
3
Order By: Relevance
“…Studies have shown that PAHs are highest in a similar environment where an indoor source (cooking or space heating or environmental tobacco smoke) dominate [33,34]. The level of PM 2.5 bound ∑ 11 PAHs observed in this study is lower in the kitchen environment than previous studies [22,24,27,32], but higher than the ambient levels measured in Europe and America [33,35]; even though the number of investigated PAHs vary. Different factors, such as ventilation rate, kitchen type and space, measurement duration, measurement activity etc.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Studies have shown that PAHs are highest in a similar environment where an indoor source (cooking or space heating or environmental tobacco smoke) dominate [33,34]. The level of PM 2.5 bound ∑ 11 PAHs observed in this study is lower in the kitchen environment than previous studies [22,24,27,32], but higher than the ambient levels measured in Europe and America [33,35]; even though the number of investigated PAHs vary. Different factors, such as ventilation rate, kitchen type and space, measurement duration, measurement activity etc.…”
Section: Discussioncontrasting
confidence: 71%
“…Several studies have reported concentrations of PAHs in the combustion zone (the kitchen) where the levels are known to be highest [18,[22][23][24][25][26][27][28] but one that characterize PAHs in the kitchen, outdoor and living room in such an overriding condition in a typical developing country has not been reported to our knowledge. The present report was part of a broader study that investigated the prevalence of acute respiratory infections in women and children potentially caused by smoke from wood and charcoal stoves in Western Sierra Leone [29].…”
Section: Introductionmentioning
confidence: 99%
“…PAHs in the environment are largely products of the incomplete combustion of petroleum, oil, coal, and wood (Edwards 1983). Sources in the urban environment include industrial emissions and wastes (Marvin et al 2000), power plants, wood and coal, home heating with fuel oil (Sims and Overcash 1983;Ansari et al 2010), vehicles (Takada et al 1990;Rogge et al 1993;Marr et al 1999;Kose et al 2008), mineral/crude oil extraction and petroleum refining processes (Yassaa and Cecinato 2005), as well as pavement sealants, also known as sealcoat (Mahler et al 2005;Peter et al 2009). Recognition of these anthropogenic sources is very important for improving city management.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, benzene concentration in indoor kitchen using wood fuel was found to be signifi cantly lower ( p < 0.01) in comparison to dung fuel used in variety of Indian kitchen facilities ( 89 , 90 ( 91 ).…”
Section: Domestic Fuelmentioning
confidence: 94%